Acute Effect of Four Different Warm-Up Protocols Using Foam Rolling (Foam Roller) on Lower Limb Strength Training Performance: An Experimental Study - Simões, Fernando (2021)
Introduction: Warm-up is often used to prepare the individual for strength training the main activity. Nowadays, foam rolling (FR) has been used as a warm-up strategy.Objective: The aim of the study was to compare the acute effect of four different warm-up protocols with and without the use of FR, on agonist and antagonist in the lower limbs’ muscles, in relation to performance in strength training.Methods: Experimental cross-sectional study, with a convenience sample, consisting of 12 physically active adult men evaluated in four experimental protocols: 1) Agonist FR - consisting of two sets of 30 seconds of FR in the quadriceps and a specific warm-up in the chair stent with 50% of the maximum load. Subsequently, the four series protocol was performed until voluntary muscle failure in the extensor chair; 2) Antagonistic FR - the same protocol was performed, however, with the RF applied to the hamstrings; 3) Combined protocol – FR was applied to the quadriceps/hamstrings and, subsequently, the same stimulus to the extensor chair; 4) Traditional protocol - only the stimulus on the extension chair was applied. Descriptive analyzes of data were presented as mean and standard deviation, and the one-way ANOVA test for repeated measures was applied.Results: There were no significant differences between protocols regarding performance in the volume of lower limb repetitions.Conclusion: Acutely, the RF applied to both antagonists and agonists compared to the traditional warm-up performed directly on the extensor chair does not change performance in strength training.